Penyuluhan pentingnya fase pra-analitik di bidang Patologi Anatomi di Kota Prabumulih - Murti, Krisna; Ramkita, Nora (Fakultas Kedokteran Universitas Sriwijaya, 2023)
The procedure for making preparations in the Anatomical Pathology Laboratory consists of three stages, including the pre-analytical process. The impact of pre-analytical process errors can lead to misdiagnosis and treatment. This community service is located at AR Bunda Hospital Prabumulih City, on Saturday, October 15, 2022 in the form of educational seminars, discussions and hands-on workshops to practice the correct tissue fixation and lamellation procedures. The activity was held in conjunction with the 60th Anniversary of the Faculty of Medicine, Sriwijaya University and the Prabumulih City Government. The seminar participants were active enough to ask questions and discuss. There were 51 participants, coming from 4 hospitals, namely Prabumulih Hospital (31.4%), AR Bunda Hospital (31.4%), Pertamina Prabumulih Hospital (19.6%), Fadillah Prabumulih Hospital (9.8%), and from other institutions around 7.8%, consisting of room nurses, general practitioners, dental nurses, operating room nurses, pharmacy, and laboratory workers. An increase in participants' knowledge by 15% was obtained based on pre-test and post-test results, so it is expected that the tissue processing process in the Anatomic Pathology Laboratory can produce paraffin blocks of good quality, immunohistochemical examinations to be accurate, and patient tissue diagnosis to be more precise.